An Artificial Polyacrylonitrile Coating Layer Confining Zinc Dendrite Growth for Highly Reversible Aqueous Zinc‐Based Batteries - Chen, Peng; Yuan, Xinhai; Xia, Yingbin; Zhang, Yi; Fu, Lijun; Liu, Lili; Yu, Nengfei; Huang, Qinghong; Wang, Bin; Hu, Xianwei; Wu, Yuping; Ree, Teunis (Advanced science, 2021)
Aqueous rechargeable zinc‐metal‐based batteries are an attractive alternative to lithium‐ion batteries for grid‐scale energy‐storage systems because of their high specific capacity, low cost, eco‐friendliness, and nonflammability. However, uncontrollable zinc dendrite growth limits the cycle life by piercing the separator, resulting in low zinc utilization in both alkaline and mild/neutral electrolytes. Herein, a polyacrylonitrile coating layer on a zinc anode produced by a simple drop coating approach to address the dendrite issue is reported. The coating layer not only improves the hydrophilicity of the zinc anode but also regulates zinc‐ion transport, consequently facilitating the uniform deposition of zinc ions to avoid dendrite formation. A symmetrical cell with the polymer‐coating‐layer‐modified Zn anode displays dendrite‐free plating/stripping with a long cycle lifespan (>1100 h), much better than that of the bare Zn anode. The modified zinc anode coupled with a Mn‐doped V2O5 cathode forms a stable rechargeable full battery. This method is a facile and feasible way to solve the zinc dendrite problem for rechargeable aqueous zinc‐metal batteries, providing a solid basis for application of aqueous rechargeable Zn batteries. A polyacrylonitrile (PAN)Z coating layer is employed to confine zinc dendrite growth for rechargeable aqueous zinc‐based batteries. The cyclability and Coulombic efficiency of the zinc anode porous PAN coating layer show that the polymer coating film is a feasible artificial membrane for a dendrite‐free zinc anode.